Sustainable Packaging and Its Role in Minimizing Environmental Footprint - AV, Subeesh.; Viswanath, Theertha; Vaseem, Mohammed; K, Subha.; K, Dr.Monisha.; K. P. , Dr. Ramya (International Journal of Aquatic Research and Environmental Studies, 2026)
The ever-increasing global environmental crisis has spurred an industrial design paradigmatic shift towards sustainable packaging, being the leading area of future design innovation development(United Nations Environment Programme, 2021). This research examines the change from traditional, linear waste-based, models to a comprehensive framework that will help reduce the detrimental impacts on the environment and resource depletion(Ellen MacArthur Foundation, 2017). Rather than just commenting about the 160 million tons of global waste produced,this research examines the successful structuring of the LCA (Life Cycle Assessment), material sciences and regulatory strategies(World Bank, 2018). The study assesses whether biodegradable polymers, fiber-based substrates, and plant-derived alternatives are technically and economically feasible as “green” materials(Vincenzo Siracusa et al., 2008). The interpretations of the findings are based upon Circular Economy principles and consider how design engineering must balance between materials’ performance characteristics and the scalability of those characteristics systemically(Organisation for Economic Co-operation and Development, 2022). There is also a significant tension between regulation and consumer behaviour; therefore, achieving true environmental stewardship requires aligning policy with the viability within the marketplace(European Commission, 2020). This research seeks to clarify how industries can achieve their operational goals while protecting the environment over time (International Organization for Standardization, 2006).
Keywords: Sustainable Packaging, Circular Economy, Life Cycle Assessment (LCA), Material innovation, Waste Mitigation, Environmental Supervision. Biodegradable Polymers. Ecological Influence